A structural review on reduced switch count and hybrid multilevel inverters - Mosepele, Boikhutso; Samikannu, Ravi; Amuhaya, Lilian (Frontiers in Energy Research, 2024)
Classical multilevel inverter (MLI) topologies have gained widespread interest in industry and academia because of the improved qualities they offer over their two-level counterparts. MLIs are characterized by reduced Total Harmonic Distortion (THD) and high power conversion efficiency. Classical MLI topologies, however, are not without drawbacks; generally, they require many components as the number of output waveform levels is increased, resulting in high cost and complex implementation. Furthermore, MLIs based on flying capacitors have issues with capacitor voltage balancing and high inrush currents. As a result, this has prompted researchers to develop reduced component count (RCC) or reduced switch count (RSC) and hybrid topologies to achieve high power quality, but at reduced cost and complexity in comparison to classical MLI topologies. This article evaluates the merits and demerits of recently proposed reduced switch count and hybrid topologies, identifies challenges and opportunities, and proposes further research and development for the improvement of multilevel inverters. This review paper will be helpful to those conducting research in the field of MLI technology.